Failure of secretin release in patients with duodenal ulcer. Issue 5950 (18th January 1975) - Bloom, S R; Ward, A S
Abstract : The release of secretin was studied in 12 normal subjects and 23 patients suffering from proved duodenal ulceration. After infusing acid directly into the duodenum mean plasma levels (plus or minus S.E.M.) of secretin rose in normal subjects to 52.6 plus or minus 4.8 ng/1 at six minutes but to only 37.5 plus or minus 3.6 ng/1 in duodenal-ulcer patients, a significant difference. The impairment of secretin release was as great in patients with a recent onset as in those who had had symptoms of a duodenal ulcer for a long time, raising the possibility of it being a primary defect. Patients who smoked 20 or more cigarettes a day had a particularly reduced secretin release, in accord with the greater incidence of ulcers in heavy smokers.